2009
DOI: 10.1021/bm900003f
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Access to Biocompatible Block Copolymers from SG1-Based Aliphatic Polyester Macro-Alkoxyamines

Abstract: SG1-based poly(d,l-lactide) (PLA) or poly(epsilon-caprolactone) (PCL) macro-alkoxyamines were synthesized and further used as macroinitiators for nitroxide-mediated polymerization (NMP) of 2-hydroxyethyl (meth)acrylate (HE(M)A) to obtain the corresponding PLA- or PCL-PHE(M)A block copolymers. First, a PLA-SG1 macro-alkoxyamine was prepared by 1,2-intermolecular radical addition (IRA) of the MAMA-SG1 (BlocBuilder) alkoxyamine onto acrylate end-capped PLA previously prepared by ring-opening polymerization. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…We opted for a block copolymer design, as a physical blending of the two incompatible homopolymers would only result in a non-valid biomaterial displaying a macrophase separation. Our synthesis approach, based on a previous work realized in our laboratory [72,73], relied on the use of a PLA-SG1 (N-tert-butyl-N-(1-diethylphosphono-2,2-dimethylpropyl)aminoxyl) macroalkoxyamine. Such a molecule is able to initiate polymerization of HEMA (Scheme 1) through nitroxide-mediated polymerization (NMP), which is usually used as a controlled/living radical polymerization technique [74,75].…”
Section: Degradabilitymentioning
confidence: 99%
“…We opted for a block copolymer design, as a physical blending of the two incompatible homopolymers would only result in a non-valid biomaterial displaying a macrophase separation. Our synthesis approach, based on a previous work realized in our laboratory [72,73], relied on the use of a PLA-SG1 (N-tert-butyl-N-(1-diethylphosphono-2,2-dimethylpropyl)aminoxyl) macroalkoxyamine. Such a molecule is able to initiate polymerization of HEMA (Scheme 1) through nitroxide-mediated polymerization (NMP), which is usually used as a controlled/living radical polymerization technique [74,75].…”
Section: Degradabilitymentioning
confidence: 99%
“…All these results confirm that the PHEMA derivatives contained a PLA side chain. 14,15 In the 1 H NMR spectra of the PHEMA-g-(PLA-DPPE) copolymer ( Figure 2C), the signal at about 0.9 ppm was attributed to the terminal methyl proton of the DPPE moiety. Peaks at 1.2-1.6 ppm were attributed to methyl protons of the DPPE moiety.…”
Section: Dovepressmentioning
confidence: 99%
“…[5][6][7][8][9] However, the mechanical properties of PHEMA hydrogels do not fit the requirements for many structural applications. Therefore, amphiphilic polymers consisting of PHEMA and biodegradable polyesters, ie, poly(L-lactide) (PLLA), 10,11 poly(D,L-lactide), [12][13][14] poly(glycolic acid), poly(ε-caprolactone), 15,16 and polystyrene, have been synthesized. 17 These copolymers can be obtained through ring-opening polymerization, atom transfer radical polymerization, 11,18,19 A 2 B 2 PCl/acrylate miktoarm polymers, 20 or use of a protective group, eg, a trimethylsilyl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Bian et al reported the controlled polymerization of the related 2‐hydroxyethyl acrylate by NMP using MONAMS initiator with SG1 in bulk and in N , N ‐dimethylformamide (DMF) solution . Clément et al reported the homopolymerization of HEMA using a SG1‐based aliphatic polyester macroalkoxyamines . Not surprisingly, the homopolymerization was not controlled, with no chain extension observed.…”
Section: Introductionmentioning
confidence: 99%